Pengaruh Adanya E-Commerce terhadap Kesejahteraan Masyarakat Melalui Variabel Pengangguran di Indonesia - Dhita Diana Dewi; Asri Yuniar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of e-commerce on people's welfare through unemployment variables in Indonesia using Structural Equation Modeling (SEM) with a Partial Least Square (PLS) approach. The current development of information technology has created new types and business opportunities where business transactions are increasingly carried out electronically. Ecommerce is a type of electronic business mechanism that focuses on individual-based business transactions using the internet as a medium for exchanging goods or services between two institutions and direct consumers, bypassing the constraints of space and time which have so far been dominant. With the existence of the internet, in this case e-commerce, it is hoped that it will be able to reduce the unemployment rate in Indonesia, in order to create prosperity for the Indonesian people. It was found that all indicators weighted on each latent variable were valid and significant, with good reliability on all latent variables of community welfare, information and computer technology (e-commerce) and employment (unemployment)